2007
DOI: 10.1016/j.cub.2007.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Multiple Traditions within and between Chimpanzee Groups

Abstract: Field reports provide increasing evidence for local behavioral traditions among fish, birds, and mammals. These findings are significant for evolutionary biology because social learning affords faster adaptation than genetic change and has generated new (cultural) forms of evolution. Orangutan and chimpanzee field studies suggest that like humans, these apes are distinctive among animals in each exhibiting over 30 local traditions. However, direct evidence is lacking in apes and, with the exception of vocal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(160 citation statements)
references
References 22 publications
12
141
1
2
Order By: Relevance
“…A combination of the two also is feasible. All three hypotheses are consistent with the recent experimental demonstration that chimpanzees can engage in conformity-based cultural transmission (37,38). However, discriminating among the hypotheses will require further longitudinal fieldwork.…”
Section: O B N O B O ( P a N I S C U S )supporting
confidence: 85%
“…A combination of the two also is feasible. All three hypotheses are consistent with the recent experimental demonstration that chimpanzees can engage in conformity-based cultural transmission (37,38). However, discriminating among the hypotheses will require further longitudinal fieldwork.…”
Section: O B N O B O ( P a N I S C U S )supporting
confidence: 85%
“…In a recent study on translocation events of zoo chimpanzees (which mimics the immigration events in the wild), it was found that the immigrating individuals conform to vocalization pattern of their new group [81]. Studies in captivity have shown that adjustments based on the desire to create or maintain a positive group sense might exist in chimpanzees [64,65,82,83]. Adjusting behaviour potentially could reduce differences between the local group member and the immigrant and favour acceptance into the group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the type and amount of information chimpanzees are gleaning and replicating from an observation are still open to debate (Byrne & Russon 1998;Zentall 2006). In addition, although several studies have used increasingly complex tasks involving hierarchical steps (Whiten 2002;Whiten et al 2007;Marshall-Pescini & Whiten 2008), the complexity of the foraging task itself is typically manipulated, while the required tool remains relatively simple (e.g. a rake).…”
Section: Introductionmentioning
confidence: 99%